Oral Cancer Knowledge Assessment: Newly Graduated versus Senior Dental Clinicians - Gisele Pavão Spaulonci; Ricardo Salgado de Souza; Vanessa Gallego Arias Pecorari; Luciano Lauria Dib (International Journal of Dentistry)
The present study assessed the level of dentists’ knowledge regarding oral cancer in the city of São Paulo, Brazil. A questionnaire was used to compare the level of knowledge among newly graduated and senior clinicians. A total of 20,154 e-mails were correctly delivered to the dentists registered in the database of the Regional Dentistry Council of São Paulo, and 477 (2.36%) responses were received. This sample consisted of 84 newly graduated clinicians and 105 senior clinicians. For the statistical analysis, the chi-square test and the logistic regression analysis were performed with α = 0.05, and the results were described herein. According to their knowledge level, the results were statistically different between the groups, since 19% of the newly graduated clinicians were evaluated with knowledge grade A (excellent) in comparison to 6.7% of the senior clinicians. In spite of the results indicated that newly graduated clinicians’ knowledge regarding oral cancer was 2.1 times higher, 34.5% of the professionals in this group had regular or poor knowledge on the subject, and several questions relating to clinical characteristics and risk factors indicated that there still exist some knowledge gaps, demonstrating that there is a need for further studies and information activities addressing oral cancer.